Electrical properties of strained off-stoichiometric Cu–Cr–O delafossite thin films - Moreira, Marco; Crêpellière, Jonathan; Polesel-Maris, Jérôme; Leturcq, Renaud; Guillot, Jérôme; Fleming, Yves; Lunca-Popa, Petru (Journal of physics. Condensed matter, 2024)
Off-stoichiometric Cu-Cr-O delafossite thin films with different thicknesses were grown by metal organic chemical vapor deposition on substrates with different coefficients of thermal expansion. Seebeck thermoelectric coefficient and resistivity measurements were performed on the range of 300-850 K. A qualitative change in the temperature-dependence of the resistivity is observed at the temperature corresponding to the deposition process, where the transition from tensile to compressive strain takes place. Arrhenius plots reveal different slopes in these two thermal ranges. The fact that the shift is more pronounced for the thinner films might indicate the induced strain plays a role in changing electrical behaviour. Furthermore, changes below 0.1% in electrical mobility were measured when the strain is induced by mechanical bending.